Classic infantile Pompe patients approaching adulthood: a cohort study on consequences for the brain. (24th March 2018) - Ebbink, Berendine J; Poelman, Esther; Aarsen, Femke K; Plug, Iris; Régal, Luc; Muentjes, Carsten; van der Beek, Nadine A M E; Lequin, Maarten H; van der Ploeg, Ans T; van den Hout, Johanna M P
Abstract : Aim: To examine the long‐term consequences of glycogen storage in the central nervous system (CNS) for classic infantile Pompe disease using enzyme replacement therapy. Method: Using neuropsychological tests and brain magnetic resonance imaging (MRI), we prospectively assessed a cohort of 11 classic infantile Pompe patients aged up to 17 years. Results: From approximately age 2 years onwards, brain MRI showed involvement of the periventricular white matter and centrum semiovale. After 8 years of age, additional white‐matter abnormalities occurred in the corpus callosum, internal and external capsule, and subcortical areas. From 11 years of age, white‐matter abnormalities were also found in the brainstem. Although there seemed to be a characteristic pattern of involvement over time, there were considerable variations between patients, reflected by variations in neuropsychological development. Cognitive development ranged from stable and normal to declines that lead to intellectual disabilities. Interpretation: As treatment enables patients with classic infantile Pompe disease to reach adulthood, white‐matter abnormalities are becoming increasingly evident, affecting the neuropsychological development. Therefore, we advise follow‐up programs are expanded to capture CNS involvement in larger, international patient cohorts, to incorporate our findings in the counselling of parents before the start of treatment, and to include the brain as an additional target in the development of next‐generation therapeutic strategies for classic infantile Pompe disease. What this paper adds: In our long‐term survivors treated intravenously with enzyme replacement therapy, we found slowly progressive symmetric white‐matter abnormalities. Cognitive development varied from stable and normal to declines towards intellectual disabilities. What this paper adds: In our long‐term survivors treated intravenously with enzyme replacement therapy, we found slowly progressive symmetric white‐matter abnormalities. Cognitive development varied from stable and normal to declines towards intellectual disabilities. This article is commented on by Schoser on page536 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.